Ejecta From the Orientale Basin at the Chang'E‐4 Landing Site. Issue 3 (3rd February 2021) - Xiao, Zhiyong; Ding, Chunyu; Xie, Minggang; Cai, Yuzhen; Cui, Jun; Zhang, Ke; Wang, Juntao
Abstract: Radargrams obtained by the Yutu‐2 rover reveal that the post‐mare deposits at the Chang'E‐4 landing site are ∼45 m thick, consistent with estimations based on orbital observations. Besides obvious ejecta from Finsen, polarized interpretations exist on whether or not the Alder crater is another contributor to the post‐mare deposits, although predicted thicknesses of ejecta from all potential source craters are not adequately large compared to observations. We recognize that the rover has been exploring along a shared crater wall of two secondaries from Finsen. Mechanics of secondary impacts suggests that the discontinuous layers of coarse and fine materials observed in the radargram are older than Finsen. Cross‐cutting relationships and crater density comparisons show that Alder is older than the mare basalts, and the Orientale basin was the major source for the post‐mare materials. Lower‐crust materials excavated by Orientale constituted a substantial portion of the surface regolith detected by the rover. Plain Language Summary: Understanding surface processes at the lunar farside and revealing potential compositions related with SPA are two scientific targets of the Chang'E‐4 mission. Orbital observations and radargrams obtained by the rover show that the mare basalts at the landing area are covered by > 30 m thick deposits. Finsen has delivered bright rays to this area, but whether or not Alder is another source has been debated. Considering all potential sources that even include Alder, predicted thickness of post‐mare materials is substantially less than observations. We recognize that Yutu‐2 is exploring along the shared wall of two secondaries from Finsen, and subsurface materials are older than Finsen. Orientale's secondaries are traceable on top of Alder. The crater density on Orientale's ejecta deposits is comparable with that of the mare surface at the landing site, and morphological comparison of secondaries indicates that substantial ejecta had been deposited in Von Kármán before the volcanism in Leibnitz was ceased. The limited time window suggests that Orientale's ejecta were the only suitable source for the post‐mare materials, forming the discontinuous layers of coarse and fine materials revealed in radargrams. Surface regolith examined by Yutu‐2 should contain lower‐crust materials that were excavated by Orientale. Key Points: The Yutu‐2 rover has been exploring along the rim of Finsen's secondaries, and pre‐Finsen materials dominate the subsurface Crater density comparisons reveal that Orientale is a major source of the post‐mare ejecta, explaining the radargram obtained Surface regolith detected by Yutu‐2 is dominated by lower‐crust materials ejected by Orientale, not related with SPA